2002
DOI: 10.1507/endocrj.49.75
|View full text |Cite
|
Sign up to set email alerts
|

Castration Induces Apoptosis in the Mouse Epididymis during Postnatal Development.

Abstract: The effect of castration on apoptosis in the mouse epididymis during postnatal development was examined. The weight of the epididymis slowly increased from day 0 (day of birth) to day 20 after birth, followed by a rapid increase thereafter. Castration on days 0, 5, 10, 20, 30, 40 and 60 increased apoptotic indices (percentages of apoptotic cells) of epithelia of the caput (head), corpus (body), and cauda (tail) epididymis, their apoptotic indices reaching maximal levels on day 2 after castration with the excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Our previous studies [13,14] showed that castration of prepubertal mice induced the lesser extents of apoptosis in the male accessory sex organs such as SV and Ep Castrated male and female mice were given 5 daily injections of TP and E 2 , respectively. Body weight of mice and weights of the male accessory sex organs and the uterus on day 1 (the day following the last injection) were measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies [13,14] showed that castration of prepubertal mice induced the lesser extents of apoptosis in the male accessory sex organs such as SV and Ep Castrated male and female mice were given 5 daily injections of TP and E 2 , respectively. Body weight of mice and weights of the male accessory sex organs and the uterus on day 1 (the day following the last injection) were measured.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the effect of Fos on production of steroid hormones by gonads, we examined apoptosis after the cessation of administration of androgen or estrogen to castrated mice. In addition, we also compared apoptosis in epithelia of the accessory sex organs of adult c-fos knockout mice with apoptosis in young normal mice because the body weights of adult c-fos knockout mice were much lighter than those of adult normal mice, suggesting the retarded development of adult c-fos-knockout mice and because our previous studies [13,14] showed that the extents of apoptosis in the accessory sex organs of young mice after castration were much less than those of adult mice, indicating that the extents of apoptosis in the accessory sex organs differ depending on the developmental stages of mice.…”
mentioning
confidence: 99%
“…At postnatal ages, acute withdrawal of androgens after orchidectomy results in apoptosis of epididymal epithelial principal cells (14,15) and dedifferentiation of the caput epididymal epithelium to a 'precursor' state (16), demonstrating that androgens are important for maintenance of epithelial cell identity. However, whether this impact of testosterone withdrawal is due to direct action on the epithelial cells or indirect action via the stromal cells remains unclear, as both cell types express AR.…”
mentioning
confidence: 99%
“…Administration of testosterone to wt and TMF À/À mice Six wt mice at the age of 18 weeks and 6 TMF À/À age-matched mice were divided into four groups: three wt and three TMF À/À mice were treated each with a control, 0.1 ml oily solution (vehicle)/day/mouse without testosterone, three wt and three TMF À/À mice were treated each with 0.5 mg/day/mouse of a testosterone-enanthate solution (Bayer pharmaceuticals), (Fan and Robaire, 1998;Takagi-Morishita et al, 2002). All solutions were injected daily, intra peritoneally (ip), using a 1 ml syringe with a 25G needle, for 12 days.…”
Section: Immunohistochemical and Immunocytochemical Detection Of Prolmentioning
confidence: 99%
“…Depletion of elongating spermatids, spermatids retention and Leydig cell hyperplasia are features of testosterone depletion (Creasy, 1997(Creasy, , 2001. Similarly, apoptotic death of the epididymal epithelium is seen in orchidectomized mice (Fan and Robaire, 1998;Takagi-Morishita et al, 2002) and in rats with reduced testosterone (Creasy, 2001). To test this possibility, serum testosterone levels were determined in eleven wt males with the average age of 30 weeks, as well as in eleven TMF À/À male mice of the same age.…”
Section: Distribution Of Tmf/ara160 In the Epididymismentioning
confidence: 99%